(untitled) (Global Journal of Human-Social Science, 2023)
This paper addresses how the predominantly atypical nature of cultural and creative work CCW freelance contractor casual once-off or part-time basis is overlaid or impacted on by informality in the African context The research presented here on Live Music is part of a larger study undertaken on commission from ILO Promoting Decent Work in the African Cultural and Creative Economy which focused on 5 sectors cultural heritage dance fashion film and tv and live music in all 5 African sub-regions North Africa Central Africa East Africa West Africa and Southern Africa respectively The paper offers a conceptual framework consisting of the triad of the atypical nature of work in the CCEs precariousness and informality against the backdrop of a Decent Work agenda The focus is on the views of players and practitioners in the live music ecosystem about the nature of work in the live music ecosystem in South Africa It concludes with a set of policy recommendations that are distinct for two reasons first rather than conventional measures to formalise the informal economy it suggests shining a spotlight on the specificities of live music work understanding its unique value chain and adopting measures to engage more productively with the informal actors throughout the value chain second rather than highlighting deficits it suggests greater government support for associations trade unions and employer bodies for the live music ecosystem to bring the decent work discussion into conversation with representative and organised